2020
DOI: 10.5194/amt-13-877-2020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of urban aerosol pollution over the Moscow megacity by the MAIAC aerosol product

Abstract: Abstract. We estimated the distribution of aerosol optical thickness (AOT) with a spatial resolution of 1 km over the Moscow megacity using the MAIAC aerosol product based on MODIS satellite data (Lyapustin et al., 2018) for the warm period of the year (May–September, 2001–2017). AERONET (Aerosol Robotic Network)-based validation of satellite estimates near the city centre at Moscow_MSU_MO and over the Moscow suburbs at Zvenigorod revealed that MAIAC AOT at 0.47 µm is in agreement with AERONET AOT though under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
(69 reference statements)
8
11
0
Order By: Relevance
“…We showed that the columnar aerosol characteristics during the 420 intensive spring campaigns on the whole are close to those during the warm period of the year. However, AODs are slightly smaller compared with the average values for these months over the 2001-2020 period, which is in the agreement with the observed negative AOD trend in Moscow megacity (Zhdanova et a., 2020, Chubarova et al, 2016. A reduction in fine mode AOD fraction may be associated with a decrease in the emissions of urban aerosol precursor gases in recent years (Zhdanova et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We showed that the columnar aerosol characteristics during the 420 intensive spring campaigns on the whole are close to those during the warm period of the year. However, AODs are slightly smaller compared with the average values for these months over the 2001-2020 period, which is in the agreement with the observed negative AOD trend in Moscow megacity (Zhdanova et a., 2020, Chubarova et al, 2016. A reduction in fine mode AOD fraction may be associated with a decrease in the emissions of urban aerosol precursor gases in recent years (Zhdanova et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…The April-May period of 2018-2019 is 225 characterized by slightly lower AOD500, which is in an agreement with a negative AOD500 trend in Moscow in recent years (Zhdanova et al,2020;Chubarova et al, 2016). The lower fraction of fine mode aerosol (64% compared to 71-73%) may also indicate the decrease in the formation of secondary aerosol due to the effective reduction of urban gas precursor emissions in Moscow (Zhdanova et al, 2020). However, in general, the aerosol conditions in April and May of 2018-2019 correspond to those during warm period with a slightly reduced AOD500 and its fine mode fraction, which corresponds to the observed 230 trends of purification of the Moscow atmosphere in recent years.…”
Section: Aerosol Characteristics In Moscow According To Long-term Aer...supporting
confidence: 82%
See 1 more Smart Citation
“…In the complex situation of the plurality of emissions, an important research task remains in the Moscow megacity environment for the assessment of the air quality and potential sources through aerosol composition analyses. Moscow aerosol pollution has been studied using a special AeroRadCity-2018 experiment (Chubarova et al, 2019) and satellite data with the application of new MAIAC/MODIS aerosol algorithm with a 1-km resolution (Zhdanova et al, 2020). An advanced source apportionment for this environment was performed using combined Fourier-transform infrared spectroscopy data and statistical principal component analysis (Popovicheva et al, 2020b).…”
Section: Anthropogenic Emissions and Environmental Pollution In Russiamentioning
confidence: 99%
“…The main and most studied optical characteristic of aerosols is the aerosol optical depth (AOD) of the atmosphere. Many authors [1][2][3][4][5][6][7] have analyzed the interannual variations and seasonal variability of different parameters of the atmospheric transparency over Russia. In [4], the results of long-term studies (1995-2017) of the physical properties and chemical composition of atmospheric aerosols in the Baikal region in three sites are considered.…”
Section: Introductionmentioning
confidence: 99%